Comparative study on the microplastics abundance, characteristics, and possible sources in yellow clams of different demographic regions of the northwest coast of India - Naidu, Bejawada Chanikya; Xavier, K.A.Martin; Shukla, Satya Prakash; Jaiswar, Ashok Kumar; Nayak, Binaya Bhusan (Journal of hazardous materials letters, 2022)
Microplastics have become ubiquitous on the planet and are considered one of the biggest threats to life on earth. Several recent studies have addressed the serious risks that microplastics can pose to human health. In this study, the microplastic content and spatial variations in number, size, colour, and polymers from a highly urbanized cosmopolitan, urban, and rural coastal locations of the northwest Indian coast were documented using yellow clams. The mean incidence of microplastics across all the stations among the clams is found to be one of the highest ever reported worldwide, which is 35.93 MPs items/g in soft tissue parts and 91.42 MPs items/individual. The clams were found to have a higher microplastic diversity integrated index (MDII) and Microplastic index (MPI). The majority of the microplastics observed were fibres and fragments, belonged to the size range of 1–100 µm (51.36%), and were identified as HDPE, polystyrene, polymethyl methacrylate, polyvinyl chloride, polyamide, and polypropylene. The clam condition index (CI) was recorded high at the rural coast with lower population and lowest at the megacity having greater population which may indicate the negative effect of MPs on clams growth. [Display omitted] •Microplastics in clams of the megacity was about four times higher than the other coasts.•The majority of the microplastics were of size below 100 µm (51.36%) in all samples.•Condition Index of clams reduced with the increased population around its coast.•Microplastic index of the studied megacity was one of the highest ever reported in the world.•Anthropogenic activities have pronounced effect on MPs abundance than fisheries activities.